3D Body Twin: Improving Human Gait Visualizations Using Personalized Avatars - Zieger, Daniel; Güthlein, Florian; Henningson, Jann-Ole; Jakob, Verena; Gaßner, Heiko; Shanbhag, Julian; Fleischmann, Sophie; Miehling, Jörg; Wartzack, Sandro; Eskofier, Björn; Winkler, Jürgen; Egger, Bernhard; et al. (ShapeMI 2024, 2024)
We propose an interactive visualization and reconstruction system for gait pattern analysis that creates a more realistic visualization of the patient than contemporary stick figure-like representations. It supports thorough gait pattern analysis, and enables unbiased inter- and intra-patient comparisons as well as longitudinal studies. Our system takes as input 3D motion capture data, but can be further constrained using readily available metadata or layman-accessible measurements. A statistical shape model is then fitted to the motion capture and personal metadata. The result is an immediate and interactive visualization of an animated 3D twin. Our system handles different marker setups and can thus be applied to already existing data. We further show that we can infer realistic body models with only a few of markers. A survey with medical experts confirms the clinical applicability of our method. <br